Hands-on data science with R : techniques to perform data manipulation and mining to build smart analytical models using R /: techniques to perform data manipulation and mining to build smart analytical models using R. (2018) - Lanzetta, Vitor Bianchi; Dasgupta, Nataraj; Anjoleto Farias, Ricardo
No abstract available